Evolutive an regressive soil sequences for assessment of soil degradation in desertifield areas of Canary Islands (Spain) - Guerra, J.A.; Arbelo, C.D.; Mora, J.L.; Notario, J.S. (Sociedade & Natureza, 2005)
The assessment of soil degradation in natural ecosystems must necessarily be performed from a non-conventional perspective, focused on agricultural productivity. Thus, the assessment of soil degradation in natural ecosystems requires the definition of standards with which to compare other soils and thus evaluate their quality. In order to define these standards and manage appropriately the processes involved in the degradation and variation of soil quality, it is necessary to understand and establish in detail the genetic processes that have taken place in that area and have led to the formation of a mature soil, which would be considered to be standard, as a non-degraded soil. In accordance with these ideas, we present in this work the evolutive and regressive succession of the soils and examples of the utilization of this methodology to evaluate soil degradation in arid zones and those in high desertification risk in the Canary Islands.